Literatur Review: Peran Aplikasi SAAS Dalam Kegiatan Bisnis E-Commerce - Hasyim Ratsanjani, M.; Fitria Risnandari, Isma; Widya Sulaiman, Thirsya; Meida Hersianty, Venny (CV. Lafadz Jaya, 2022)
The existence of cloud computing will clearly cause changes in the way information technology systems work in a business. This is due to cloud computing through the concept of virtualization, standardization and other fundamental features that can reduce costs, simplify the management of information technology services and speed up service delivery. One of the cloud computing infrastructures, namely Software as a Service (SaaS), is currently the choice for many companies that are developing their business, especially in the E-Commerce business. As a typical form of cloud services, SaaS has been leading the adoption of cloud to enable E-Commerce by the industry. The development of a framework for modeling complex business systems as a SaaS model in the Cloud has proven to be very effective. Literature review is carried out based on issues, methodologies, and similarities. Of the 12 studies conducted, several methods are used with algorithms that are appropriate to the existing problems. Based on 12 studies, it was found that there are several factors that encourage the use of SaaS and cloud in general in business processes spread across several countries. In one of the studies, there is a method used to support SaaS-oriented business processes. Discussion: The application of the SaaS model to E-Commerce business processes provides an important and very profitable role in providing services to customers.